Implementation of government goods and services procurement using the e-purchasing method in the tegal religious court: Mediating role of supply chain in Indonesia - Suci Hartati; Imawan Sugiharto; Jamal Fakhri; Siswadi Siswadi; Ismail Suardi Wekke; Azhari Azhari; Roslina Roslina (International Journal of Supply Chain Management, 2020)
Abstract-Program Postgraduate Program in Pancasakti University Tegal. 2019. Implementation of Procurement of Government Goods and Services by E- Purchasing Method in the Tegal Religious Court. The implementation of e- procurement in various agencies makes the process of interaction between users and service providers, and the community-run easier and accelerates the process of procurement of goods. Equally important, the implementation of e-procurement has automatically improved the control system for various rules and violations. Procurement of government goods/services electronically can be done by e- tendering and e-purchasing who use electronic catalogs and supply chain plays a vital role in the e-purchasing of the goods and services. The purpose of this study is 1) examine the implementation of e-purchasing in the application of rules regarding the procurement process of goods/services through the Tegal Religious Court, 2) explain the role of supervisory institutions in the implementation of the procurement process of goods in the Tegal Religious Court in anticipation of fraud that can cause losses to the state's finances. This type of research is normative-empirical legal research using a normative approach. The type of material used is primary, secondary and tertiary legal materials. Data collection methods used are library research and field studies.The results of this study include 1) procurement of goods/services with e- purchasing method is the right system in implementing procurement because it is more transparent, effective, efficient, compared to conventional systems, but the implementation is not optimal because a) is still coordinated so that time is not enough efficient, b) in e-catalog there is no information on the number of items available, so the buyer does not know the stock directly, c) the Supreme Court has not precisely targeted domestic production due to high specifications, 2) the role of supervisory institutions is not optimal because there are still many frauds and not yet the maximum application of a whistleblower because the procurement executors and the wider community are not familiar with the procurement of goods/services.